Resin composition for coating and molded article
By using rubber-enhanced vinyl resin in the coating resin and an olefin resin modified with oxygen-containing polar functional group, the peeling, cracks and "elbow" defects of the finished coating product on the substrate are solved, and the good adhesion and high-quality appearance of the coating film are achieved, while improving the impact and thermal performance of the finished product.
Patent Information
- Application Number
- JP2021542902
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-26
- Filing Date
- 2020-08-24
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2040-08-24
AI Technical Summary
In the prior art, defects such as peeling, cracks and "elbows" of the coating film are prone to occur when manufacturing finished coating products, especially on substrates manufactured by injection molding methods, there are coating problems caused by residual stress.
The coating resin combination of a rubber-reinforced vinyl resin and an olefin resin modified with oxygen-containing polar functional group is used to combine the rubber part with the resin part through chemical bonds to improve the adhesion and weather resistance of the coating film.
Effectively inhibit peeling and cracks of the coating film, improve the appearance quality of the finished coating product, and enhance its impact and thermal performance.
Smart Images

Figure 0007669275000005 
Figure 0007669275000006 
Figure 0007669275000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition for coating suitable for producing a paintable molded article as a base molded article which is coated on the surface thereof to give a painted molded article having a good appearance. [Background technology]
[0002] 2. Description of the Related Art Conventionally, molded articles made of thermoplastic resin compositions containing rubber-reinforced vinyl resins such as ABS resins have been used in a wide range of fields such as vehicles, home appliances, and building materials because of their excellent impact resistance. In the field of vehicles, for example, spoilers, which are automobile parts, are manufactured by painting the surface of a resin molded product. Resin molded products (molded products for painting) with streamlined parts such as spoilers may have residual distortion, and when they are painted, defects called "cracks" and "popliteal" may occur on the painted surface. "Cracks" occur when, after painting a resin molded product, the paint solvent penetrates from the surface to the inside of the molded product at the part with residual distortion, causing the resin to deteriorate and cracks to occur. "Poplites" occur when the paint film hardens before the volatiles of the solvent are released from inside the crack during drying, leaving traces of air bubbles. In order to prevent "cracks" and "popliteal", when painting a resin molded product with residual distortion, the resin molded product may be heat-treated or surface-treated in advance, but this is not economical, so improvements to the molding material are being actively studied.
[0003] Patent Documents 1 and 2 disclose techniques for resin compositions suitable for coating molded articles containing rubber-reinforced vinyl resins. Patent Document 1 discloses a thermoplastic resin composition for coating, which comprises a rubber-reinforced resin composed of a copolymer resin (A1) obtained by polymerizing at least two monomers (b) selected from the group consisting of aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylic acid esters, acid anhydride monomers, and maleimide compounds in the presence of a rubber polymer (a) [A], or a blend of the copolymer resin (A1) and a (co)polymer resin (A2) obtained by polymerizing at least one monomer selected from the group consisting of the monomers (b), and [B] a mixture containing at least two copolymers of ethylene, (meth)acrylic acid esters, and carbon monoxide having different melt flow rate values, wherein the content of the mixture [B] is 3 to 70 parts by weight per 100 parts by weight of the rubber-reinforced resin [A]. Patent Document 2 discloses a thermoplastic resin composition for coating comprising (A) a polyamide resin, (B) a styrene-based resin, and (C) an olefin-based resin, wherein a molded article obtained from the resin composition has a coating adhesion of 10 or less squares in a cross-cut test using 100 squares of 1 mm x 1 mm, and the coating has a breaking strength of 350 J / m or more. Patent Document 3 discloses a coating resin composition comprising 84.9 to 98.9 parts by mass of a rubber-reinforced vinyl resin [A], 1 to 8 parts by mass of a polyester resin [B], and 0.1 to 7.1 parts by mass of an ethylene-(meth)acrylic acid ester-carbon monoxide copolymer [C] (wherein [A] + [B] + [C] = 100 parts by mass). Patent Document 4 describes a method for producing an aromatic polycarbonate resin composition containing an aromatic polycarbonate resin (A), a rubber polymer / aromatic vinyl / vinyl cyanide copolymer (B-1), and a polyolefin resin (C) as resin components, at an injection rate of 10 to 100 cm 3 / s, and surface progression coefficient of 40 to 200 cm 3 An aromatic polycarbonate resin molded article obtained by injection molding under conditions of 1000 g / s·cm is disclosed. Patent Document 5 discloses a coating resin composition which contains (A) a rubber-reinforced vinyl resin consisting of a rubber portion derived from an ethylene-α-olefin rubber polymer and a resin portion containing a structural unit derived from an aromatic vinyl compound, (B) a polyolefin resin, and (C) a polycarbonate resin, in which the contents of the rubber-reinforced vinyl resin (A), the polyolefin resin (B), and the polycarbonate resin (C) are 3 to 40 mass%, 1 to 20 mass%, and 40 to 91 mass%, respectively, when the total of these is taken as 100 mass%. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-327779 A [Patent Document 2] JP 2007-327011 A [Patent Document 3] JP 2011-256366 A [Patent Document 4] JP 2014-184720 A [Patent Document 5] JP 2019-19238 A Summary of the Invention [Problem to be solved by the invention]
[0005] The object of the present invention is to provide a resin composition for coating which can be used to produce a molded article for coating that is excellent in appearance and suppresses defects such as peeling of the coating film, and also to provide a resin composition for coating suitable for producing a base molded article that can produce a coated molded article having a good appearance and suppresses coating defects such as cracks and popping, even if a molded article (base molded article) is produced by injection molding, which tends to generate residual strain, and then painted. Another object of the present invention is to provide a resin composition for coating which can produce a molded article for coating that is excellent in impact resistance and heat resistance. [Means for solving the problem]
[0006] The present invention is illustrated below. 1. A coating resin composition comprising a thermoplastic resin, the thermoplastic resin comprising (A) a rubber-reinforced vinyl resin consisting of a rubber portion derived from a rubber polymer and a resin portion containing a structural unit derived from an aromatic vinyl compound, and (B) an olefin resin modified with a polar functional group containing an oxygen atom. 2. A coating resin composition according to item 1, wherein the content of component (B) is 0.1 to 15% by mass, relative to 100% by mass of the total amount of the thermoplastic resin. 3. A coating resin composition according to item 1 or 2, wherein the polar functional group contained in component (B) is an acid anhydride group. 4. A resin composition for coating according to any one of items 1 to 3, wherein the rubbery polymer used in forming component (A) comprises a diene-based rubbery polymer. 5. The coating resin composition according to any one of items 1 to 4, wherein the thermoplastic resin further comprises an aromatic vinyl copolymer (excluding component (A)) containing a structural unit derived from an aromatic vinyl compound. 6. The coating resin composition according to any one of items 1 to 5, wherein the thermoplastic resin further comprises a polycarbonate resin. 7. A molded article comprising the coating resin composition according to any one of items 1 to 6. 8. The molded product according to item 7, which is an automobile part. Effect of the Invention
[0007] The resin composition for coating of the present invention can produce a molded article for coating that is excellent in appearance and suppresses problems such as peeling of the coating film. In addition, even if a molded article (substrate-side molded article) is produced by injection molding, which tends to generate residual strain, and then painted, the coating film has excellent adhesion and coating defects (cracks, popping, etc.) are suppressed, making the composition suitable for producing a substrate-side molded article that produces a coated molded article with good appearance. Furthermore, the coating resin composition of the present invention makes it possible to produce a coating molded article having excellent impact resistance and heat resistance. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 shows a test piece used in a peel test in the Examples, where (1) is a bottom view and (2) is a cross-sectional view taken along line XX in (1). [Diagram 2] FIG. 2 is a perspective view of a test piece used in a coating test in the Examples. [Diagram 3] 3 is a plan view (1), a side view (2), and a cross-sectional view (3) taken along line YY of the test piece in FIG. 2. [Figure 4] FIG. 2 is a diagram illustrating cracks formed in a coating film of a coating test piece obtained in a coating test in the Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below. In this specification, "(meth)acrylic" means acrylic and methacrylic, "(meth)acrylate" means acrylate and methacrylate, "(meth)acryloyl group" means acryloyl group and methacryloyl group, "(meth)allyl group" means allyl group and methallyl group, and "(co)polymer" means homopolymer and copolymer.
[0010] The coating resin composition of the present invention is a thermoplastic resin composition containing a thermoplastic resin (hereinafter also referred to as "thermoplastic resin (X)") essentially consisting of the following components (A) and (B): (A) A rubber-reinforced vinyl resin comprising a rubber portion derived from a rubber polymer (hereinafter also referred to as "rubber portion (a1)") and a resin portion containing a structural unit derived from an aromatic vinyl compound (hereinafter also referred to as "resin portion (a2)"). (B) Olefin resin modified with a polar functional group containing an oxygen atom The thermoplastic resin (X) may consist of the above components (A) and (B), and may further contain other thermoplastic resins (described below) as necessary. The coating resin composition of the present invention may also contain additives (described below).
[0011] The component (A) is preferably a graft resin in which a rubber portion (a1) and a resin portion (a2) are chemically bonded to each other. This graft resin will be described in detail below.
[0012] The rubbery polymer forming the rubbery portion (a1) may be a homopolymer or a copolymer, so long as it is rubbery (has rubber elasticity) at 25° C. The rubbery polymer may be either a diene polymer (hereinafter referred to as a "diene rubbery polymer") or a non-diene polymer (hereinafter referred to as a "non-diene rubbery polymer"). These rubbery polymers may be either crosslinked or non-crosslinked.
[0013] Examples of the diene rubbery polymer include homopolymers such as polybutadiene, polyisoprene, and polychloroprene; styrene-butadiene copolymers such as styrene-butadiene copolymers, styrene-butadiene-styrene copolymers, acrylonitrile-butadiene copolymers, and acrylonitrile-styrene-butadiene copolymers; and styrene-isoprene copolymers such as styrene-isoprene copolymers, styrene-isoprene-styrene copolymers, and acrylonitrile-styrene-isoprene copolymers. These copolymers may be block copolymers or random copolymers.
[0014] Examples of the non-diene rubbery polymer include ethylene-α-olefin copolymers, urethane rubbers, acrylic rubbers, silicone rubbers, silicone-acrylic IPN rubbers, and hydrogenated polymers obtained by hydrogenating (co)polymers containing structural units derived from conjugated diene compounds (however, the hydrogenation rate is 80% or more). These copolymers may be block copolymers or random copolymers.
[0015] The non-diene rubbery polymer is preferably an ethylene-α-olefin copolymer, and this ethylene-α-olefin copolymer may be either a copolymer comprising structural units derived from ethylene and structural units derived from an α-olefin, or a copolymer comprising structural units derived from ethylene, structural units derived from an α-olefin, and structural units derived from another monomer. Examples of the α-olefin include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-hexadecene, and 1-eicosene. These α-olefins can be used alone or in combination of two or more. The number of carbon atoms of the α-olefin is preferably 3 to 20, more preferably 3 to 12, and even more preferably 3 to 8. Examples of other monomers include non-conjugated diene compounds such as alkenylnorbornenes, cyclic dienes, and aliphatic dienes. The ethylene-α-olefin copolymer is preferably a copolymer comprising structural units derived from ethylene, structural units derived from an α-olefin, and structural units derived from another monomer, and more preferably a copolymer comprising structural units derived from ethylene, structural units derived from an α-olefin, and structural units derived from an alkenylnorbornene such as 5-ethylidene-2-norbornene or a cyclic diene such as dicyclopentadiene.
[0016] In the present invention, the component (A) preferably contains a rubber-reinforced vinyl resin (hereinafter referred to as "rubber-reinforced vinyl resin (A1)") consisting of a rubbery portion (a1) derived from a diene-based rubbery polymer and a resin portion (a2) containing structural units derived from an aromatic vinyl compound. In a further preferred embodiment, the component (A) contains a rubber-reinforced vinyl resin (hereinafter referred to as "rubber-reinforced vinyl resin (A2)") consisting of a rubbery portion (a1) derived from an ethylene-α-olefin-based rubbery polymer and a resin portion (a2) containing structural units derived from an aromatic vinyl compound.
[0017] On the other hand, the resin portion (a2) constituting the component (A) contains a structural unit derived from an aromatic vinyl compound (hereinafter referred to as "structural unit (u1)"). The aromatic vinyl compound is not particularly limited as long as it has at least one vinyl bond and at least one aromatic ring. However, it does not have a substituent such as a functional group. Examples of the aromatic vinyl compound include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, β-methylstyrene, ethylstyrene, p-tert-butylstyrene, vinyltoluene, vinylxylene, vinylnaphthalene, etc. Among these, styrene and α-methylstyrene are preferred.
[0018] The resin portion (a2) may contain only one type of the structural unit (u1), or may contain two or more types. The resin portion (a2) may be composed of the structural unit (u1) and a structural unit derived from a vinyl monomer other than an aromatic vinyl compound (hereinafter referred to as "structural unit (u2)").
[0019] Examples of other vinyl monomers that form the structural unit (u2) include vinyl cyanide compounds, (meth)acrylic acid ester compounds, maleimide compounds, carboxyl group-containing unsaturated compounds, unsaturated acid anhydrides, amino group-containing unsaturated compounds, amide group-containing unsaturated compounds, hydroxyl group-containing unsaturated compounds, and oxazoline group-containing unsaturated compounds.
[0020] Examples of the vinyl cyanide compound include acrylonitrile, methacrylonitrile, ethacrylonitrile, α-ethylacrylonitrile, and α-isopropylacrylonitrile.
[0021] Examples of the (meth)acrylic acid ester compound include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, and benzyl (meth)acrylate.
[0022] Examples of the maleimide-based compound include maleimide, N-methylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-dodecylmaleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-benzylmaleimide, N-naphthylmaleimide, N-cyclohexylmaleimide, etc. When a structural unit derived from a maleimide-based compound is introduced into a polymer chain, for example, a method of copolymerizing maleic anhydride and then imidizing the copolymer can be applied.
[0023] Examples of the unsaturated acid anhydride include maleic anhydride, itaconic anhydride, citraconic anhydride, and 2,3-dimethylmaleic anhydride. Examples of the carboxy-containing unsaturated compound include (meth)acrylic acid, ethacrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, and cinnamic acid.
[0024] Examples of the amino group-containing unsaturated compound include aminoethyl acrylate, propylaminoethyl acrylate, dimethylaminomethyl acrylate, diethylaminomethyl acrylate, 2-dimethylaminoethyl acrylate, aminoethyl methacrylate, propylaminoethyl methacrylate, dimethylaminomethyl methacrylate, diethylaminomethyl methacrylate, 2-dimethylaminoethyl methacrylate, phenylaminoethyl methacrylate, p-aminostyrene, N-vinyldiethylamine, N-acetylvinylamine, acrylamine, methacrylamine, and N-methylacrylamine. Examples of the amide group-containing unsaturated compound include acrylamide, N-methylacrylamide, methacrylamide, and N-methylmethacrylamide.
[0025] Examples of the hydroxy group-containing unsaturated compound include (meth)acrylic acid esters having a hydroxy group, such as hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, and polypropylene glycol mono(meth)acrylate; o-hydroxystyrene, m-hydroxystyrene, p-hydroxystyrene, o-hydroxy-α-methylstyrene, m-hydroxy-α-methylstyrene, and p-hydroxy-α-methyl Examples of the copolymer include styrene, 2-hydroxymethyl-α-methylstyrene, 3-hydroxymethyl-α-methylstyrene, 4-hydroxymethyl-α-methylstyrene, 4-hydroxymethyl-1-vinylnaphthalene, 7-hydroxymethyl-1-vinylnaphthalene, 8-hydroxymethyl-1-vinylnaphthalene, 4-hydroxymethyl-1-isopropenylnaphthalene, 7-hydroxymethyl-1-isopropenylnaphthalene, 8-hydroxymethyl-1-isopropenylnaphthalene, p-vinylbenzyl alcohol, 3-hydroxy-1-propene, 4-hydroxy-1-butene, cis-4-hydroxy-2-butene, trans-4-hydroxy-2-butene, and 3-hydroxy-2-methyl-1-propene.
[0026] Examples of the epoxy group-containing unsaturated compound include glycidyl (meth)acrylate, 3,4-oxycyclohexyl (meth)acrylate, vinyl glycidyl ether, allyl glycidyl ether, methallyl glycidyl ether, monoglycidyl maleate, diglycidyl maleate, monoglycidyl itaconate, diglycidyl itaconate, monoglycidyl allyl succinate, diglycidyl allyl succinate, glycidyl p-styrenecarboxylate, 2-methylpropenyl glycidyl ether, and styrene-p-glycidyl ether.
[0027] Examples of the oxazoline group-containing unsaturated compound include vinyloxazoline, 4-methyl-2-vinyl-2-oxazoline, 5-methyl-2-vinyl-2-oxazoline, 2-vinyl-4,4-dimethyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 4-methyl-2-isopropenyl-2-oxazoline, 5-methyl-2-isopropenyl-2-oxazoline, and 2-isopropenyl-4,4-dimethyl-2-oxazoline.
[0028] When the resin portion (a2) contains the structural unit (u2), it may contain only one type of the structural unit (u2), or it may contain two or more types of the structural unit (u2). From the viewpoints of the appearance, mechanical strength and chemical resistance of the molded article to be painted, it is preferable that the structural unit (u2) contains a structural unit derived from a vinyl cyanide compound.
[0029] When the resin portion (a2) contains the structural unit (u2), the contents of the structural unit (u1) and the structural unit (u2) are preferably 40 to 90 mass% and 10 to 60 mass%, more preferably 50 to 85 mass% and 15 to 50 mass%, and even more preferably 60 to 80 mass% and 20 to 40 mass%, respectively, when the total of the structural unit (u1) and the structural unit (u2) is 100 mass%.
[0030] When the component (A) is a graft resin, the graft ratio is preferably 20% or more, more preferably 30% or more, and even more preferably 35 to 65%, from the viewpoints of the appearance and mechanical strength of the molded article to be painted. The graft ratio can be calculated by the following formula. Graft rate (%) = {(ST) / T} x 100 In the above formula, S is the mass (g) of the insoluble matter obtained by adding 1 g of component (A) to 20 ml of acetone, shaking for 2 hours with a shaker, and then centrifuging to separate the insoluble matter from the soluble matter, and T is the mass (g) of the rubbery portion (a1) derived from the rubbery polymer contained in 1 g of component (A). The mass of this rubbery portion (a1) can be obtained by a method of calculation from the polymerization recipe and polymerization conversion rate, a method of determining by infrared absorption spectrum (IR), etc.
[0031] The component (A) contained in the thermoplastic resin (X) may be of one type or of two or more types. For example, it may be a combination of two or more kinds of rubber-reinforced vinyl resins (A1), a combination of two or more kinds of rubber-reinforced vinyl resins (A2), or a combination of rubber-reinforced vinyl resins (A1) and (A2).
[0032] When the component (A) is composed of rubber-reinforced vinyl resins (A1) and (A2), the proportions of these, relative to the total of the two being 100 mass%, are preferably 20 to 60 mass% and 40 to 80 mass%, more preferably 30 to 50 mass% and 50 to 70 mass%, respectively, from the viewpoint of coatability.
[0033] When the component (A) is a graft resin, the graft resin can be one produced by emulsion polymerization, suspension polymerization, solution polymerization, or bulk polymerization of a monomer component containing an aromatic vinyl compound in the presence of a rubber polymer. The reaction product produced by this method usually contains the graft resin, which is the component (A), and a resin in which the rubber portion and the resin portion are not chemically bonded. The latter resin is the component (D) described below, and when the reaction product is used as a production raw material, the resulting coating resin composition contains the components (A) and (D).
[0034] The component (B) is an olefin-based resin that mainly contains a structural unit derived from an olefin (hereinafter referred to as "structural unit (v1)") and is modified with a polar functional group containing an oxygen atom (hereinafter referred to as "oxygen atom-containing polar functional group"). Examples of the oxygen atom-containing polar functional group include a hydroxyl group, a carboxyl group, an acid anhydride group, an ester group, an epoxy group, an amide group, a nitro group, an oxazoline group, a sulfonic acid group, a sulfonamide group, and a phosphoric acid group. The type and total number of the oxygen atom-containing polar functional groups contained in the component (B) are not particularly limited. The oxygen atom-containing polar functional group preferably contains an acid anhydride group. The component (B) may further contain a functional group that does not contain an oxygen atom.
[0035] Examples of the component (B) include a copolymer (hereinafter referred to as "modified resin (B1)") containing the structural unit (v1) and a structural unit derived from a monomer having an oxygen atom-containing polar functional group (hereinafter referred to as "structural unit (v2)"), and a composite resin in which at least a part of the surface of a non-modified olefin resin is coated with a (co)polymer containing the structural unit (v2). Among these, the modified resin (B1) is preferred.
[0036] Examples of olefins forming the structural unit (v1) contained in the modified resin (B1) include ethylene, propylene, 1-butene, 2-butene, isobutylene, 1-pentene, 2-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 2,3-dimethyl-2-butene, 1-butene, 1-hexene, 1-octene, 1-nonene, and 1-decene. The structural unit (v1) contained in the modified resin (B1) may be of only one type or may be of two or more types. When the structural unit (v1) contained in the modified resin (B1) is of only one type, it is preferably a structural unit derived from propylene. Furthermore, when the modified resin (B1) contains a plurality of structural units (v1), examples of combinations of olefins include ethylene and propylene; ethylene and 1-butene; ethylene and 4-methyl-1-pentene; ethylene and 1-hexene; propylene and 4-methyl-1-pentene; 1-butene and 4-methyl-1-pentene; 1-hexene and 4-methyl-1-pentene; ethylene and 1-octene; propylene and 1-butene; 4-methyl-1-pentene and 1-octene, etc.
[0037] Examples of the monomer having an oxygen atom-containing polar functional group that forms the structural unit (v2) contained in the modified resin (B1) include the hydroxyl group-containing unsaturated compounds, carboxyl group-containing unsaturated compounds, unsaturated acid anhydrides, amide group-containing unsaturated compounds, and oxazoline group-containing unsaturated compounds exemplified as the monomer that forms the structural unit (u2) that may be contained in the component (A), as well as other carboxyl group-containing unsaturated compounds (such as incomplete esterification products of unsaturated compounds having two or more carboxyl groups). Among these, unsaturated acid anhydrides are preferred, and maleic anhydride is particularly preferred. The structural unit (v2) contained in the modified resin (B1) may be of only one type, or may be of two or more types.
[0038] The content of the structural unit (v2) in the modified resin (B1) is preferably 1 to 20 mass %, more preferably 5 to 15 mass %, from the viewpoints of dispersibility and coatability of the modified resin (B1) in the composition.
[0039] The modified resin (B1) is preferably a copolymer having a hydrophobic segment composed of the structural unit (v1) and a hydrophilic segment composed of the structural unit (v2).
[0040] The component (B) contained in the thermoplastic resin (X) may be of only one type, or may be of two or more types.
[0041] The content of component (B) in the thermoplastic resin (X) is preferably 0.1 to 15 mass%, more preferably 0.2 to 12 mass%, even more preferably 0.3 to 9 mass%, still more preferably 0.4 to 6 mass%, and particularly preferably 0.5 to 3 mass%, based on 100 mass% of the total amount of the thermoplastic resin (X), from the viewpoints of coatability and molded appearance (peeling).
[0042] As described above, the thermoplastic resin (X), which is the main component of the coating resin composition of the present invention, can contain other thermoplastic resins. Examples of other thermoplastic resins include vinyl (co)polymers (excluding unmodified polyolefin resins) that do not contain rubber parts and are not included in component (A) and contain structural units derived from vinyl monomers, polycarbonate resins, unmodified polyolefin resins, modified polyolefin resins not included in component (B), polyester resins, polyamide resins, etc. Among these, polycarbonate resins (hereinafter also referred to as "component (C)") and vinyl (co)polymers (hereinafter also referred to as "component (D)") are preferred. When the thermoplastic resin (X) contains other thermoplastic resins, the upper limit of the content of the other thermoplastic resins relative to the entire thermoplastic resin (X) is preferably 90 mass %, more preferably 88 mass %.
[0043] The component (C) is not particularly limited as long as it is a polycarbonate resin having a carbonate bond in the main chain, and may be an aromatic polycarbonate or an aliphatic polycarbonate. It may also be an aliphatic carbonate containing an aromatic ring. In the present invention, from the viewpoint of impact resistance and heat resistance before and after coating, aromatic polycarbonates are preferred. The component (C) may be one whose terminals are modified to an R-CO- group or an R'-O-CO- group (R and R' both represent organic groups).
[0044] Examples of the aromatic polycarbonate that can be used include those obtained by melting an aromatic dihydroxy compound and a carbonic acid diester to cause ester exchange (ester exchange reaction), those obtained by an interfacial polycondensation method using phosgene, and those obtained by a pyridine method using a reaction product of pyridine and phosgene.
[0045] The aromatic dihydroxy compound may be any compound having two hydroxy groups in the molecule, and examples thereof include dihydroxybenzenes such as hydroquinone and resorcinol, 4,4'-biphenol, 2,2-bis(4-hydroxyphenyl)propane (hereinafter referred to as "bisphenol A"), 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl-3-methylphenyl)propane, 2,2-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)methane, 1,1-bis(p-hydroxyphenyl)ethane, 2,2-bis(p-hydroxyphenyl)butane, 2,2-bis(p-hydroxyphenyl)pentane, 1,1-bis(p-hydroxyphenyl)cyclohexane, 1,1-bis(p-hydroxyphenyl)-4-isopropane, and the like. Examples of the bis(p-hydroxyphenyl)sulfonylcyclohexane, 1,1-bis(p-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(p-hydroxyphenyl)-1-phenylethane, 9,9-bis(p-hydroxyphenyl)fluorene, 9,9-bis(p-hydroxy-3-methylphenyl)fluorene, 4,4'-(p-phenylenediisopropylidene)bisphenol, 4,4'-(m-phenylenediisopropylidene)bisphenol, bis(p-hydroxyphenyl)oxide, bis(p-hydroxyphenyl)ketone, bis(p-hydroxyphenyl)ether, bis(p-hydroxyphenyl)ester, bis(p-hydroxyphenyl)sulfide, bis(p-hydroxy-3-methylphenyl)sulfide, bis(p-hydroxyphenyl)sulfone, bis(3,5-dibromo-4-hydroxyphenyl)sulfone, bis(p-hydroxyphenyl)sulfoxide, etc. These can be used alone or in combination of two or more.
[0046] Among the above aromatic hydroxy compounds, compounds having a hydrocarbon group between two benzene rings are preferred. In this compound, the hydrocarbon group may be a halogen-substituted hydrocarbon group. In addition, the benzene ring may be one in which a hydrogen atom bonded to a carbon atom constituting the benzene ring is substituted with a halogen atom. Therefore, examples of the above compounds include bisphenol A, 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl-3-methylphenyl)propane, 2,2-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)methane, 1,1-bis(p-hydroxyphenyl)ethane, and 2,2-bis(p-hydroxyphenyl)butane. Among these, bisphenol A is particularly preferred.
[0047] Examples of the carbonate diester used to obtain an aromatic polycarbonate by transesterification include dimethyl carbonate, diethyl carbonate, di-tert-butyl carbonate, diphenyl carbonate, ditolyl carbonate, etc. These can be used alone or in combination of two or more.
[0048] The average molecular weight and molecular weight distribution of the component (C) are not particularly limited as long as the composition has moldability. The molecular weight of the component (C) is preferably 10,000 to 50,000, more preferably 15,000 to 30,000, and even more preferably 17,500 to 27,000 in terms of viscosity average molecular weight (Mv) calculated from the solution viscosity measured at 25°C using methylene chloride as a solvent. The melt mass flow rate (hereinafter also referred to as "MFR") of the above component (C) according to ISO 1133 is preferably 1 to 70 g / 10 min, more preferably 2.5 to 50 g / 10 min, and even more preferably 4 to 30 g / 10 min, under conditions of a temperature of 240°C and a load of 10 kg.
[0049] The component (C) contained in the thermoplastic resin (X) may be of one type or of two or more types.
[0050] When the thermoplastic resin (X) contains the component (C), the content of the component (C) is preferably 400 to 700 parts by mass, more preferably 500 to 600 parts by mass, based on 100 parts by mass of the component (A). In a composition containing 400 parts by mass or more of the component (C), the content of the component (B) is preferably 5 to 110 parts by mass, more preferably 7 to 80 parts by mass, based on 100 parts by mass of the component (A).
[0051] The component (D) may be, for example, a (co)polymer containing a structural unit derived from at least one selected from the group consisting of aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylic acid ester compounds, maleimide compounds, unsaturated acid anhydrides, carboxyl group-containing unsaturated compounds, amino group-containing unsaturated compounds, amide group-containing unsaturated compounds, hydroxyl group-containing unsaturated compounds, oxazoline group-containing unsaturated compounds, and vinyl halide compounds. In the present invention, the component (D) is preferably a copolymer containing a structural unit derived from an aromatic vinyl compound and a structural unit derived from at least one selected from the group consisting of vinyl cyanide compounds, (meth)acrylic acid ester compounds, maleimide compounds, unsaturated acid anhydrides, carboxyl group-containing unsaturated compounds, amino group-containing unsaturated compounds, amide group-containing unsaturated compounds, hydroxyl group-containing unsaturated compounds and oxazoline group-containing unsaturated compounds, and is more preferably a copolymer such as an acrylonitrile-styrene copolymer, an acrylonitrile-α-methylstyrene copolymer, an acrylonitrile-styrene-α-methylstyrene copolymer, an acrylonitrile-styrene-methyl methacrylate copolymer, an acrylonitrile-α-methylstyrene-methyl methacrylate copolymer, an acrylonitrile-styrene-N-phenylmaleimide copolymer, a styrene-methyl methacrylate copolymer or a styrene-N-phenylmaleimide copolymer. In the present invention, the above-mentioned component (D) is particularly preferably a copolymer consisting of a structural unit derived from an aromatic vinyl compound and a structural unit derived from a vinyl cyanide compound (hereinafter referred to as "aromatic vinyl-based copolymer (D1)"), a copolymer consisting of a structural unit derived from an aromatic vinyl compound and a structural unit derived from a maleimide-based compound, or a copolymer consisting of a structural unit derived from an aromatic vinyl compound, a structural unit derived from a vinyl cyanide compound, and a structural unit derived from a maleimide-based compound.
[0052] A preferred structure of the aromatic vinyl copolymer (D1) is shown below from the viewpoint of coatability. The content ratios of the structural units derived from aromatic vinyl compounds and the structural units derived from vinyl cyanide compounds, when the total of both is taken as 100 mass%, are preferably 60 to 90 mass% and 10 to 40 mass%, more preferably 63 to 80 mass% and 20 to 37 mass%, further preferably 65 to 75 mass% and 25 to 35 mass%, and particularly preferably 67 to 73 mass% and 27 to 33 mass%, respectively.
[0053] The component (D) contained in the thermoplastic resin (X) may be of one type or of two or more types.
[0054] When the thermoplastic resin (X) contains the component (D), the content of the component (D) is preferably 40 to 320 parts by mass, more preferably 100 to 320 parts by mass, based on 100 parts by mass of the component (A). In a composition containing 40 parts by mass or more of the component (D), the content of the component (B) is preferably 1 to 110 parts by mass, more preferably 2 to 80 parts by mass, based on 100 parts by mass of the component (A). When the thermoplastic resin (X) does not contain the component (C), the content of the component (B) is preferably 1 to 55 parts by mass, more preferably 2 to 45 parts by mass, based on 100 parts by mass of the component (A).
[0055] The unmodified polyolefin resin is preferably an unmodified (co)polymer comprising at least one structural unit derived from an α-olefin having 2 or more carbon atoms. In the present invention, a particularly preferred unmodified polyolefin resin is a polyolefin resin comprising at least one structural unit derived from an α-olefin having 2 to 10 carbon atoms.
[0056] Examples of the α-olefin include ethylene, propylene, butene-1, pentene-1, hexene-1, 3-methylbutene-1, 4-methylpentene-1, 3-methylhexene-1, etc. Among these, ethylene, propylene, butene-1, 3-methylbutene-1 and 4-methylpentene-1 are preferred, and propylene is particularly preferred.
[0057] Examples of the unmodified polyolefin resin include polyethylene, polypropylene, ethylene-propylene copolymer, polybutene-1, and ethylene-butene-1 copolymer.
[0058] The unmodified polyolefin resin may be crystalline or amorphous, and preferably has a crystallinity of 20% or more at room temperature as determined by X-ray diffraction. The molecular weight of the non-modified polyolefin resin is not particularly limited, but from the viewpoint of the appearance and mechanical strength of the molded article to be painted, the MFR (temperature 190°C, load 2.16 kg) according to ISO 1133 is preferably 0.1 to 50 g / 10 min, more preferably 0.5 to 30 g / 10 min, and it is preferable that the resin has a molecular weight corresponding to each value.
[0059] The polyester resin is not particularly limited as long as it is a resin having an ester bond in the main chain of the molecule. The polyester resin is preferably a saturated polyester resin. The saturated polyester resin may be a homopolyester or a copolymer polyester.
[0060] Examples of the homopolyester include polyalkylene terephthalates such as polyethylene terephthalate (PET), polypropylene terephthalate (PPT), polybutylene terephthalate (PBT), polyhexamethylene terephthalate, polycyclohexane-1,4-dimethyl terephthalate, and polyneopentyl terephthalate; and polyalkylene naphthalates such as polyethylene isophthalate, polyethylene naphthalate, polybutylene naphthalate, and polyhexamethylene naphthalate. The copolymer polyester may be, for example, a copolymer polyester containing mainly alkylene terephthalate units and / or alkylene naphthalate units.
[0061] In the present invention, the ratio of the rubbery portion (a1) constituting the component (A) to the thermoplastic resin (X) is preferably 1 to 50 mass%, more preferably 3 to 40 mass%, further preferably 5 to 30 mass%, and particularly preferably 7 to 21 mass%, from the viewpoints of fluidity (moldability) and impact resistance.
[0062] The coating resin composition of the present invention may contain additives as described above. Examples of the additives include fillers, plasticizers, antioxidants, UV absorbers, antiaging agents, flame retardants, stabilizers, weathering agents, light stabilizers, heat stabilizers, antistatic agents, water repellents, oil repellents, antibacterial agents, preservatives, colorants (pigments, dyes, etc.), etc. For example, fillers may have shapes such as chunks, fibers (lines), and scales, and a composition containing a fibrous or scale-like filler is one of the preferred embodiments. Examples of fibrous fillers include wollastonite, glass fiber, milled glass fiber fiber, carbon fiber, milled carbon fiber fiber, zinc oxide whiskers, aluminum borate whiskers, potassium titanate whiskers, etc. Examples of scale-like fillers include glass flakes, mica, talc, etc.
[0063] The coating resin composition of the present invention can be produced by kneading the raw material components using various extruders, Banbury mixers, kneaders, rolls, feeder ruders, etc., and can be made into pellets of a predetermined shape, etc. The temperature of the equipment during kneading is selected depending on the type and amount of the raw material components, but is usually 180° C. to 300° C. The method of using the raw material components is not particularly limited, and each component may be mixed and kneaded at once, or may be mixed and kneaded in multiple stages.
[0064] The molded article of the present invention is characterized by containing a coating resin composition. The molded article of the present invention can be produced by subjecting the coating resin composition to a conventionally known molding method such as injection molding, injection compression molding, press molding, extrusion molding, coextrusion molding, sheet extrusion molding, profile extrusion molding, vacuum molding, blow molding, compression molding, cast molding, roll molding, etc. The coating resin composition of the present invention is highly productive and is also suitable for injection molding, which tends to cause residual distortion when a large molded article is produced.
[0065] The molded article of the present invention is excellent in shape stability and appearance because defects such as peeling are suppressed, and further, has excellent impact resistance. In addition, it has a heat distortion temperature of 70° C. or more and has excellent heat resistance. Furthermore, the molded article of the present invention is used as a base molded article for painting, and when the surface is painted, a painted molded article having excellent adhesion of the paint film and excellent paint appearance can be obtained.
[0066] The method for forming the coating film on the molded product of the present invention is not particularly limited, and conventionally known coating methods such as spray coating, electrostatic coating, powder coating, and electrodeposition coating can be applied. The coating material used for coating is also not particularly limited, and may be either a liquid coating material or a powder coating material, but is preferably a liquid coating material, and is particularly preferably an oil-based coating material. Examples of the base resin include acrylic resin, phenolic resin, alkyd resin, aminoalkyd resin, vinyl chloride resin, silicone resin, fluororesin, unsaturated polyester resin, epoxy resin, polyurethane resin, melamine resin, acrylic urethane resin, acrylic melamine resin, and polyester melamine resin. The thickness of the coating film on the resulting coated molded article depends on the type of paint, etc., but is usually 10 to 100 μm from the viewpoint of coating appearance.
[0067] The coated molded article has excellent adhesion of the coating film to the substrate, the molded article of the present invention, has a good appearance, and is suppressed from causing coating defects such as cracks and popping. Furthermore, even if the coated molded article comes into contact with water or a cleaning agent, the coating film does not peel off or deteriorate. Therefore, the coated molded article may be used in either a closed environment or outdoors, and is particularly suitable as an automobile part (interior or exterior part). EXAMPLES
[0068] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples as long as it does not deviate from the gist of the present invention. In the following, parts and % are by weight unless otherwise specified.
[0069] 1. Raw material ingredients The raw materials used in the following Examples and Comparative Examples are as follows: The graft ratio was measured according to the method described above.
[0070] 1-1. Rubber-reinforced vinyl resin ABS resin and AES resin were used as raw resins containing rubber-reinforced vinyl resin.
[0071] 1-1-1.ABS resin (P-1) Into the flask, 54 parts of polybutadiene rubber latex (average particle size 270 nm) calculated as solids, 6 parts of styrene-butadiene copolymer rubber latex (styrene unit content 25%, average particle size 550 nm) calculated as solids were added, and 150 parts of ion-exchanged water, 7 parts of styrene, 3 parts of acrylonitrile, and 0.2 parts of t-dodecyl mercaptan were further added and the temperature inside the flask was raised to 60°C. After that, a solution of 0.2 parts of sodium pyrophosphate, 0.01 parts of ferrous sulfate heptahydrate, and 0.4 parts of glucose dissolved in 20 parts of ion-exchanged water was added, and 0.1 parts of cumene hydroperoxide was further added to initiate polymerization. The temperature of the hot bath was maintained at 70°C. After polymerization for 1 hour, 22 parts of styrene, 8 parts of acrylonitrile, 0.5 parts of t-dodecyl mercaptan, and 0.2 parts of cumene hydroperoxide were continuously added over 2 hours, and polymerization was continued for another hour to complete the reaction. The obtained copolymer latex was coagulated by adding sulfuric acid, washed with water, and dried to obtain a powdered resin composition. The graft ratio of the diene rubber-reinforced vinyl resin contained in the obtained resin composition was 33%, and the intrinsic viscosity [η] of the ungrafted acrylonitrile-styrene copolymer (acetone soluble portion) (measured in methyl ethyl ketone at 30°C) was 0.21 dl / g.
[0072] 1-1-2.ABS resin (P-2) This resin composition was obtained by emulsion polymerization of styrene and acrylonitrile in the presence of polybutadiene rubber with a gel fraction of 86% and an average particle size of 290 nm. The graft ratio of the diene rubber-reinforced vinyl resin in this resin composition was 53%, and the polybutadiene rubber content in the diene rubber-reinforced resin was 60%, the amount of acrylonitrile units was 10%, and the amount of styrene units was 30%. The ungrafted acrylonitrile-styrene copolymer (acetone soluble portion) contained 25% and 75% of acrylonitrile units and 75% of styrene units, respectively, and its intrinsic viscosity [η] (measured in methyl ethyl ketone at 30°C) was 0.37 dl / g.
[0073] 1-1-3.AES resin (P-3) In a toluene solvent, the amount of ethylene units is 63%, the amount of propylene units is 32%, and the amount of dicyclopentadiene units is 5%. 1+4 The resin composition was obtained by polymerizing styrene and acrylonitrile in the presence of ethylene-propylene-dicyclopentadiene copolymer rubber with a viscosity modulus (at 100°C) of 33. The graft ratio of the ethylene-α-olefin rubber-reinforced vinyl resin in this resin composition was 60%, and the content of the ethylene-propylene-dicyclopentadiene copolymer rubber in the ethylene-α-olefin rubber-reinforced resin was 30%, the amount of acrylonitrile units was 24.5%, and the amount of styrene units was 45.5%. The ungrafted acrylonitrile-styrene copolymer (acetone soluble portion) contained 35% and 65% of acrylonitrile units and 65% of styrene units, respectively, and its limiting viscosity [η] (measured in methyl ethyl ketone at 30°C) was 0.4 dl / g.
[0074] 1-2. Vinyl polymers 1-2-1. Acrylonitrile-styrene copolymer (Q-1) It is an acrylonitrile-styrene copolymer containing 24% and 76% acrylonitrile units, respectively, and has a weight average molecular weight of 142000 as calculated based on polystyrene by GPC. The intrinsic viscosity [η] (measured in methyl ethyl ketone at 30°C) is 0.058 dl / g.
[0075] 1-2-2. Acrylonitrile-styrene copolymer (Q-2) It is an acrylonitrile-styrene copolymer containing 32% and 68% acrylonitrile units, respectively, and has a weight average molecular weight of 71200 as calculated based on polystyrene by GPC. The intrinsic viscosity [η] (measured in methyl ethyl ketone at 30°C) is 0.041 dl / g.
[0076] 1-2-3. Acrylonitrile-styrene copolymer (Q-3) It is an acrylonitrile-styrene copolymer containing 33% and 67% acrylonitrile units, respectively, and has a weight average molecular weight of 116,000 as calculated based on polystyrene by GPC. The intrinsic viscosity [η] (measured in methyl ethyl ketone at 30°C) is 0.053 dl / g.
[0077] 1-2-4. Acrylonitrile-α-methylstyrene copolymer (Q-4) It is an acrylonitrile-α-methylstyrene copolymer containing 25% acrylonitrile units and 75% α-methylstyrene units, respectively. The intrinsic viscosity [η] (measured in methyl ethyl ketone at 30°C) is 0.40 dl / g.
[0078] 1-3. Modified polyolefin resin (R-1) The raw material for component (B) was maleic anhydride modified polypropylene "UMEX 1010" (product name) manufactured by Sanyo Chemical Industries, Ltd. The melt viscosity at 160°C was 6000 mPa·s, and the acid value according to JIS K 0070 was 52.
[0079] 1-4. Polycarbonate resin (S-1) As the raw material for component (C), polycarbonate "NOVAREX 7022PJ" (product name) manufactured by Mitsubishi Engineering Plastics Corp. was used. The viscosity average molecular weight (Mv) was 18,700, and the MFR (temperature 240°C, load 10 kg) was 7.7 g / 10 min.
[0080] 1-5. Ethylene-acrylic ester-carbon monoxide copolymer (T-1) The ethylene-acrylic ester-carbon monoxide copolymer "Elvaloy HP661" (trade name) manufactured by Mitsui DuPont Polychemicals was used. The MFR (temperature 190°C, load 2.16 kg) according to ISO 1133 is 12 g / 10 min.
[0081] 1-6. Polybutylene terephthalate resin (T-2) Polybutylene terephthalate "DURANEX 200FP" (product name) manufactured by WinTech Polymer Co., Ltd. was used.
[0082] 1-7. Polypropylene resin (T-3) The polypropylene used was "Novatec FY4" (product name) manufactured by Japan Polypropylene Corporation. The MFR (temperature 190°C, load 2.16 kg) according to ISO 1133 was 5.0 g / 10 min.
[0083] 1-8.Additives As additives, the following antioxidants and fillers were used. 1-8-1. Phosphorus-based antioxidants (U-1) Distearyl pentaerythritol diphosphite "ADEKA STAB PEP-8" (trade name) manufactured by ADEKA Corporation was used. 1-8-2. Phosphorus-based antioxidants (U-2) Tris(2,4-di-tert-butylphenyl)phosphite "ADEKA STAB 2112" (trade name) manufactured by ADEKA Corporation was used. 1-8-3.Phenol-based antioxidants (U-3) 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate "Sumilizer GS" (trade name) manufactured by Sumitomo Chemical Co., Ltd. was used. 1-8-4.Wollastonite (U-4) Wollastonite "SH-800" (product name) manufactured by Kinsei Matec Co., Ltd. was used. 1-8-5. Talc (U-5) Talc "Microace P-3RC51" (product name) manufactured by Nippon Talc Co., Ltd. was used.
[0084] 2. Evaluation Method The coating resin compositions prepared in the Examples and Comparative Examples were subjected to injection molding to obtain test pieces or coated test pieces having shapes and sizes according to the evaluation items, after which various evaluations were carried out.
[0085] 2-1.Shock resistance The Charpy impact strength was measured according to ISO 179 at a temperature of 23°C. 2-2. Heat resistance The heat distortion temperature was measured according to ISO 75 under a load of 1.80 MPa.
[0086] 2-3. Appearance of molded product A plate-shaped test piece having a protrusion 2 using a gate was obtained using an injection molding machine "α-150" (model name) manufactured by FANUC Corporation. The resin temperature during injection molding was 260°C, the mold temperature was 50°C, and the injection speed was 80 mm / s. Next, two notches 3 (length of notch: 2 mm) were made on the left and right sides of the protruding portion 2 of the plate-shaped test piece to obtain a test piece 1 for evaluating the molded appearance shown in FIG. 1. The dimensions in the figure are as follows: L=150 mm, W=70 mm, T=3 mm, L 1 = 45mm, L 0 = 6mm, W 1 = 3 mm, T 0 The protrusion 2 was pinched with pliers and pulled in the direction of the arrow in FIG. 1(2), and the surface of the test piece 1 was visually observed to see whether peeling occurred or not, and the molded appearance was evaluated based on the following evaluation criteria. <Evaluation of molded appearance> A: No peeling occurred near the protrusion 2. B: Peeling occurred in a part near the protrusion 2. C: Peeling occurred in the area near the protrusion 2.
[0087] 2-4.Paintability A FANUC injection molding machine "α-150" (model name) was used to obtain the test piece 5 shown in Figures 2 and 3. The resin temperature during injection molding was 260°C, the mold temperature was 25°C, and the injection speed was 20 mm / s. Next, a test piece for evaluating paintability (painted test piece) was prepared according to the following procedure, and the presence or absence of painting defects such as popping or cracks as shown by reference symbol 7 in Figure 4 was visually observed on the surface, and the paintability was judged based on the following evaluation criteria. (1) Conditioning The test piece 5 shown in FIG. 2 was left in a thermostatic chamber adjusted to 23° C. for 12 hours or more to condition it. (2) Painting A paint for painting consisting of 80 parts of an acrylic resin-based paint base, 85 parts of a thinner for synthetic resin paint, and 10 parts of a hardener was spray-painted (film thickness: 20 to 30 μm) on the surface indicated by the symbol P of the test piece 5 shown in FIG. 2 and FIG. 3, and left to stand at 23° C. for 5 minutes. (3) Drying Thereafter, the coating was dried at 80° C. for 30 minutes to obtain a coated test piece.
[0088] <Evaluation of Paint Defects (Undersides)> 5: No occurrence of underarm odor was observed. 4: 1 to 5 armpits were identified. 3: 6 to 10 armpits were identified. 2:11~20 armpits were identified. 1:2More than one armpit was identified. <Evaluation of Paint Defects (Cracks)> 5: No cracks were observed at all. 4: Cracks less than 100 μm in width and less than 1 cm in length were found in one or more places only on the edge portions of the surface of the painted test piece. 3: Cracks less than 100 μm in width and 1 cm or more in length were found in one or more locations on the edge portion of the surface of the painted test piece. 2: Cracks 100 μm or more in width were found in one or more locations only on the edge portions of the surface of the painted test piece. 1: Cracks were found in one or more places on the surface of the painted test piece, regardless of the location.
[0089] <Overall evaluation of paintability> The overall evaluation was made by calculating the average of the total scores of the evaluation results for popping and cracking observed on the painted test pieces. A: More than 4.0 points and less than 5.0 points. B: More than 3.0 points and less than 4.0 points. C: More than 2.0 points and less than 3.0 points. D: 2.0 points or less.
[0090] 3. Production and evaluation of resin compositions for coating (1) Examples 1-1 to 1-9 and Comparative Examples 1-1 to 1-3 The raw materials shown in Tables 1 and 2 were mixed in a Henschel mixer in a predetermined ratio, and the mixture was fed to a twin-screw extruder "SBTN-32" (model name) manufactured by Plastics Engineering Research Institute Co., Ltd., and melt-kneaded (cylinder set temperature: 200°C to 240°C) to obtain pellets (resin composition for coating) made of a thermoplastic resin composition. The pellets were then used to measure the melt mass flow rate at a temperature of 220°C and a load of 98N in accordance with ISO 1133, and the fluidity (moldability) was evaluated. The above-mentioned various evaluations were also performed, and the results are shown in Tables 1 and 2.
[0091] [Table 1]
[0092] [Table 2]
[0093] The following can be seen from Tables 1 and 2: Comparative Examples 1-1 to 1-3 are examples that do not contain the component (B) according to the present invention, and the paintability was poor. On the other hand, Examples 1-1 to 1-9 are examples that have the configuration of the present invention, and defects such as peeling of the paint film were suppressed, and a painted molded article with excellent appearance was obtained. Among these, Example 1-7 in particular is an example that contains the component (B) according to the present invention in a preferable ratio, and a painted molded article with excellent impact resistance and heat resistance was obtained.
[0094] 4. Production and evaluation of resin compositions for coating (2) Examples 2-1 to 2-13 and Comparative Examples 2-1 to 2-3 The raw materials shown in Tables 3 and 4 were mixed in a Henschel mixer in a predetermined ratio, and the mixture was fed to a twin-screw extruder "SBTN-32" (model name) manufactured by Plastics Engineering Research Institute Co., Ltd. and melt-kneaded (cylinder set temperature: 220°C to 260°C) to obtain pellets (resin composition for coating) made of a thermoplastic resin composition. The pellets were then used to measure the melt mass flow rate at a temperature of 240°C and a load of 98N in accordance with ISO 1133, and the fluidity (moldability) was evaluated. The above-mentioned various evaluations were also performed, and the results are shown in Tables 3 and 4.
[0095] [Table 3]
[0096] [Table 4]
[0097] The following can be seen from Tables 3 and 4. Comparative Examples 2-1 to 2-3 are examples that do not contain the component (B) according to the present invention, and the paintability was poor. On the other hand, Examples 2-1 to 2-13 are examples that have the configuration of the present invention, and defects such as peeling of the coating film were suppressed, and a painted molded article with excellent appearance was obtained. Among these, Example 2-8 is particularly an example that contains the component (B) according to the present invention in a preferable ratio, and a painted molded article with good flowability, excellent moldability, impact resistance, and heat resistance was obtained. [Industrial Applicability]
[0098] Molded articles obtained from the resin composition for coating of the present invention are suitable for applications requiring impact resistance, heat resistance, molded appearance, paintability, etc., such as glazing for vehicle window members, vehicle exterior parts such as bonnets, pillars, trunk lids, canopies, spoilers and trim, vehicle interior parts such as cup holders, bezels for in-vehicle equipment and instrument panels, housings and parts for electric and electronic equipment such as (mobile) telephones, smartphones, PDAs, (portable) DVD players, (portable) personal computers, (portable) game consoles, (portable) touch panels and cameras, office automation parts such as printers and copiers, lighting equipment parts, building materials such as signs, display boards, window frames, sashes and decorative panels, pachinko machines, toys such as figures and plastic models, interior or exterior parts for industrial or industrial robots, and interior or exterior parts for vehicles (airplanes, ships, etc.) requiring a good appearance due to painted decoration. [Explanation of symbols]
[0099] 1: Test piece for evaluating molded appearance, 2: Convex part, 3: Incision, 5: Test piece for evaluating paintability, 7: Crack, P: Painted surface
Claims
1. The thermoplastic resin includes (A) a graft resin having a rubber portion derived from a diene-based rubber polymer and a resin portion including a structural unit derived from an aromatic vinyl compound, and (B) an olefin-based resin modified with maleic anhydride, The coating resin composition is characterized in that the component (B) is a maleic anhydride modified polypropylene, and the content of the component (B) is 0.5 to 6% when the total amount of the thermoplastic resin is taken as 100% by mass (provided that the coating resin composition contains a rubber-reinforced resin, an ethylene-(meth)acrylic acid ester-carbon monoxide copolymer, and polytetrafluoroethylene, and the contents of the ethylene-(meth)acrylic acid ester-carbon monoxide copolymer and the polytetrafluoroethylene are each 0.5 to 20 parts by mass per 100 parts by mass of the rubber-reinforced resin). and 0.01 to 5 parts by mass of a thermoplastic resin composition (S), and (a) 40 to 99% by mass of a hydrogenated polymer mainly composed of an aromatic vinyl compound and a conjugated diene compound, (b) 1 to 60% by mass of a block copolymer having an olefin block (b-1) and a hydrophilic polymer block (b-2), and (c) 0 to 59% by mass of a polyolefin (c-1) and / or a polyolefin modified with a functional group (c-2) (however, the total of the components (a), (b) and (c) is 100% by mass), excluding a pressure-sensitive adhesive (T).
2. 2. The coating resin composition according to claim 1, wherein the aromatic vinyl compound comprises at least one member selected from the group consisting of styrene and α-methylstyrene.
3. 3. The coating resin composition according to claim 1, wherein the graft ratio of the graft resin is 35 to 65%.
4. 4. A coating resin composition according to claim 1, wherein said diene rubber polymer comprises polybutadiene.
5. 5. The coating resin composition according to claim 1, wherein the thermoplastic resin further comprises an aromatic vinyl copolymer (excluding component (A)) containing a structural unit derived from an aromatic vinyl compound.
6. 6. The coating resin composition according to claim 1, wherein the thermoplastic resin further comprises a polycarbonate resin.
7. A molded article comprising the coating resin composition according to any one of claims 1 to 6.
8. The molded article according to claim 7, which is an automobile part.
Citation Information
Patent Citations
Polycarbonate / Polyolefin resin composition, its production and its molded product
JP1998298420A
Styrene polymer composition
JP1999012415A
Polycarbonate-based resin composition and molding product
JP1999092648A
Aqueous anticorrosive composition, anticorrosively treated steel and its production
JP1999172189A
Flame-retardant resin composition
JP1999256001A